Effects of a High Fat Diet and Voluntary Wheel Running Exercise on Cidea and Cidec Expression in Liver and Adipose Tissue of Mice. - Thomas H Reynolds; Sayani Banerjee; Vishva Mitra Sharma; Jacob Donohue; Sandrine Couldwell; Alexandra Sosinsky; Ashton Frulla; Allegra Robinson; Vishwajeet Puri (PLoS ONE, 2015)
Cidea and Cidec play an important role in regulating triglyceride storage in liver and adipose tissue. It is not known if the Cidea and Cidec genes respond to a high fat diet (HFD) or exercise training, two interventions that alter lipid storage. The purpose of the present study was to determine the effect of a HFD and voluntary wheel running (WR) on Cidea and Cidec mRNA and protein expression in adipose tissue and liver of mice. A HFD promoted a significant increase in Cidea and Cidec mRNA levels in adipose tissue and liver. The increase in Cidea and Cidec mRNAs in adipose tissue and liver in response to a HFD was prevented by WR. Similar to the changes in Cidea mRNA, Cidea protein levels in adipose tissue significantly increased in response to a HFD, a process that was, again, prevented by WR. However, in adipose tissue the changes in Cidec mRNA did not correspond to the changes in Cidec protein levels, as a HFD decreased Cidec protein abundance. Interestingly, in adipose tissue Cidea protein expression was significantly related to body weight (R=.725), epididymal adipose tissue (EWAT) mass (R=.475) and insulin resistance (R=.706), whereas Cidec protein expression was inversely related to body weight (R=-.787), EWAT mass (R=-.706), and insulin resistance (R=-.679). Similar to adipose tissue, Cidea protein expression in liver was significantly related to body weight (R=.660), EWAT mass (R=.468), and insulin resistance (R=.599); however, unlike adipose tissue, Cidec protein levels in liver were not related to body weight or EWAT mass and only moderately associated with insulin resistance (R=-.422, P=0.051). Overall, our findings indicate that Cidea is highly associated with adiposity and insulin resistance, whereas Cidec is related to insulin sensitivity. The present study suggests that Cide proteins might play an important functional role in the development of obesity, hepatic steatosis, as well as the pathogenesis of type 2 diabetes.